NILAI BAIMAN, BAUNTUNG, BATUAH, DAN BAADAB DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SMP NEGERI 25 BANJARMASIN - Yunika Perdana (JURNAL SOCIUS, 2018)
AbstractThe implementation of education positions us to understand the values of life. In understanding it, we can explore the cultural values that we already have. This article described the importance of integrating cultural values through social studies subjects so that learners have a change in the aspects of cognitive, affective, and psychomotor. Baiman 'as the core of the Banjar culture has the potential to increase love for God and  the  truth,  because  baiman'  is  a  view  of  life  that  aims  to  remember  the existence of God. Bauntung 'which is a form of skill to live independently. Batuah for the purpose of life of learners beneficial to others and the State of Indonesia. Baadab make learners become beings who have noble character.Keywords: Baiman, Bauntung, Batuah, Baadab, social studies AbstrakPelaksanaan pendidikan memposisikan kita untuk memahami nilai-nilai kehidupan. Dalam memahaminya, kita bisa menggali nilai budaya yang sudah dimiliki. Tulisan ini bertujuan ntuk mendeskirpsikan pentingnya mengintegrasikan nilai budaya melalui mata pelajaran IPS agar peserta   didik   memiliki   perubahan   pada   aspek   kognitif,   afektif,   maupun psikomotor. Baiman’ sebagai inti budaya Banjar memiliki potensi yang dapat meningkatkan cinta kepada Allah dan kebenaran, sebab baiman’ merupakan pandangan hidup yang bertujuan mengingat adanya Allah. Bauntung’ yang merupakan wujud keterampilan agar hidup bisa mandiri.   Batuah agar tujuan hidup peserta didik bermanfaat bagi orang lain dan Negara Indonesia. Baadab menjadikan peserta didik menjadi insan yang berakhlak mulia.Kata Kunci: Baiman, Bauntung, Batuah, Baadab, dan IPS